Cecal volvulus: about a case - Trostchansky, J (Cirugía del Uruguay, 2020)
A case of mechanical occlusion of the small intestine is reported upon. Attention is drawn to the importance of X-ray survey as a diagnostic aid. Treatment involved devolvulation and pexia, in view of the general and humoral state of the .patient.